Need Analysis of Waste Transporter Fleet in Pati District - Aris Krisdiyanto; Kemmala Dewi; Diky Rohmat Setiawan; Ariel Kriswandatu; Althea Serafim Kriswandatu (International Journal of Social Service and Research (IJSSR), 2023)
Transportation of waste to carry waste from the transfer location or from the source of the waste directly to the Final Disposal Site (TPA). In Pati Regency there is a buildup of waste from shops, trades, and markets. The purpose of this study is to determine the waste transportation system, determine the needs of the waste transportation fleet, and determine the need for the number of waste transportation fleets in 2031. The method used is Stationary Container System (SCS) is used to analyze the waste transportation fleet, Waste Generation Prediction is used to predict volume population waste generation in 2031. There are currently 18 waste transport vehicles in Pati Regency, for dump trucks with a capacity of 8 m for 2 rites/ day, for arm roll trucks with a capacity of 6 m, which is 9 units. Garbage transport vehicles needed by Pati Regency in ideal conditions with the volume of waste generated 662.09 tons/day are 86 units for dump trucks with a capacity of 8 m for 3 rites/day and 26 units of arm roll trucks with a capacity of 6 m for 3 ritations/day. Meanwhile, the need for waste transportation vehicles in 2031 with an estimated waste generation of 714.87 tons/day is 104 units of dump trucks measuring 8m for 3 rites/day and 41 units of arm roll trucks for 3 rites/day measuring 6m³ ??and garbage carts/rickshaws in 2031 based on prediction required 661 units.